2003
DOI: 10.1523/jneurosci.23-02-00652.2003
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Role of Polysialylated Neural Cell Adhesion Molecule in Photic Phase Resetting of the Mammalian Circadian Clock

Abstract: The suprachiasmatic nuclei (SCN), the location of the mammalian circadian clock, are one of the few adult brain regions that express the highly polysialylated form of neural cell adhesion molecule (PSA-NCAM). A role for the polysialic acid (PSA) component of PSA-NCAM, which is known to promote tissue plasticity, has been reported for photic entrainment of circadian rhythmicity in vivo. The in vivo results, however, do not discriminate between PSA acting upstream or downstream of the glutamatergic synapses that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 54 publications
(63 reference statements)
7
33
0
2
Order By: Relevance
“…On the other hand, Datura stramonium agglutinin that specifically reacts with Nacetylglucosamine ␀1-6 mannose (GlcNAc␀1-6Man), reacted intensely at ZT2 (supplemental Table S1), suggesting that GlcNAc␀1-6Man glycan fluctuates in an opposing manner to ␣1-2Fuc glycan. Although previous studies have shown that polysialic acid binding to NCAM has diurnal variation in the suprachiasmatic nucleus (23,24), the signal intensity of 13 lectins in the OB that had high affinity for sialic acid was identical between day and night.…”
Section: Diurnal Variation Of Glycan Structures Determined Using Amentioning
confidence: 57%
“…On the other hand, Datura stramonium agglutinin that specifically reacts with Nacetylglucosamine ␀1-6 mannose (GlcNAc␀1-6Man), reacted intensely at ZT2 (supplemental Table S1), suggesting that GlcNAc␀1-6Man glycan fluctuates in an opposing manner to ␣1-2Fuc glycan. Although previous studies have shown that polysialic acid binding to NCAM has diurnal variation in the suprachiasmatic nucleus (23,24), the signal intensity of 13 lectins in the OB that had high affinity for sialic acid was identical between day and night.…”
Section: Diurnal Variation Of Glycan Structures Determined Using Amentioning
confidence: 57%
“…In support of this model, copper has been shown to cause a delay in circadian neural activity rhythms (Yamada and Prosser, 2014). Addition of glutamate to a slice preparation of the SCN increases polySia-NCAM1 levels causing phase delays (Prosser et al, 2003). Pretreatment of this slice preparation of the SCN with endosialidase abolishes these phase delays (Prosser et al, 2003).…”
Section: Prp and Polysia-ncam1mentioning
confidence: 99%
“…Addition of glutamate to a slice preparation of the SCN increases polySia-NCAM1 levels causing phase delays (Prosser et al, 2003). Pretreatment of this slice preparation of the SCN with endosialidase abolishes these phase delays (Prosser et al, 2003). Thus, an intricate interplay between glutamate release, the circadian control of polySia-NCAM1 and PrP C levels, as well as their ability to modulate NMDA-mediated glutamate signaling might influence the circadian phase.…”
Section: Prp and Polysia-ncam1mentioning
confidence: 99%
“…Reports indicate that an unusual carbohydrate ␣2,8-linked polysialic acid (PSA), which appears to be exclusively associated with NCAM, is required for correct axonal branching and fasciculation in the peripheral nervous system (Rutishauser and Landmesser, 1996), lamination, and synaptogenesis of mossy fibers (Cremer et al, 1997;Seki and Rutishauser, 1998), structural plasticity in the hypothalamic-pituitary system (Theodosis et al, 1999), migration of neural precursor cells to the olfactory bulb (Hu et al, 1996;Chazal et al, 2000), synaptic plasticity in the CA1 region of the hippocampus (Becker et al, 1996;Muller et al, 1996;Eckhardt et al, 2000), spatial learning (Cremer et al, 1994;Becker et al, 1996), and circadian rhythm (Shen et al, 1997;Prosser et al, 2003). Here, we used heterogenotypic cultures containing wild-type and NCAM-deficient neurons to study the mechanisms underlying NCAM-driven preferential synapse formation.…”
Section: Introductionmentioning
confidence: 99%